2015
DOI: 10.1007/s13277-015-3701-y
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of FOXP2 promoter human hepatocellular carcinoma cell invasion

Abstract: Hepatocellular carcinoma (HCC) is a major health concern with a high morbidity and mortality rate worldwide. However, the mechanism underlying hepatocarcinogenesis remains unclear. Forkhead box P2 (FOXP2) has been implicated in various human cancer types. However, the role of FOXP2 in HCC remains unknown. Western blot and immunohistochemistry were used to measure the expression of FOXP2 protein in HCC and adjacent normal tissues in 50 patients. Wound healing and transwell assays were used to determine the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 47 publications
5
34
0
Order By: Relevance
“…Accordingly, we suggest that miR-196b promotes tumor progression via exerting a pro-metastatic role in HCC. FOXP2 has been recognized as a tumor suppressor and suppresses the metastasis of HCC and breast cancer (15,28). Data from the GEO database further confirmed the underexpression of FOXP2 in HCC.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Accordingly, we suggest that miR-196b promotes tumor progression via exerting a pro-metastatic role in HCC. FOXP2 has been recognized as a tumor suppressor and suppresses the metastasis of HCC and breast cancer (15,28). Data from the GEO database further confirmed the underexpression of FOXP2 in HCC.…”
Section: Discussionmentioning
confidence: 71%
“…5D), which initially suggested that the miR-196b and 3'UTR of FOXP2 may combine with each other. A recent study found that FOXP2 was prominently reduced in HCC tissues and inhibited migration and invasion of cancer cells (15). Data from the GEO database (GSE45436) demonstrated that the expression of FOXP2 in HCC tissues was notably downregulated compared to that noted in normal liver tissues (P<0.0001, Fig.…”
Section: Mir-196b Expression ----------------------------------------mentioning
confidence: 86%
“…Although the miR-122 mimic upregulated the cell proliferation, motility, and invasion activities, occludin knockdown only upregulated cell motility. Target prediction programs predict that putative miR-122 binding sequences exist in other genes involved in cell growth [e.g., p27 (36), PHD3 (37,38), and DUSP2 (39)] and invasion [e.g., CPEB1 (40), FOXP2 (41), and SOX17 (42)]. Occludin is known to mediate the MAPK signalling pathway via oncogenic proteins such as Raf (29).…”
Section: Mir-122 Promotes Mapk Signaling In Ccrcc Cell Linesmentioning
confidence: 99%
“…Numerous recent studies indicate a tumor suppressor like role for FOXP2 (Campbell et al, 2010;Cuiffo et al, 2014;Yan et al, 2015;Diao et al, 2018;Song et al, 2017;Li et al, 2019), others present evidence for an oncogene-like role of the protein (Campbell et al, 2010;Zhong et al, 2017;Wu et al, 2018;.…”
Section: Forkhead Box Protein P2 Encoded By Foxp2 Genementioning
confidence: 99%